2017
DOI: 10.1186/s40824-017-0104-8
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Ti-40Nb implant material with strontium by reactive sputtering

Abstract: BackgroundSurface functionalization of orthopedic implants with pharmaceutically active agents is a modern approach to enhance osseointegration in systemically altered bone. A local release of strontium, a verified bone building therapeutic agent, at the fracture site would diminish side effects, which could occur otherwise by oral administration. Strontium surface functionalization of specially designed titanium-niobium (Ti-40Nb) implant alloy would provide an advanced implant system that is mechanically adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Cell adhesion also plays a crucial role in the process of osseointegration. The main purpose is promoting the adhesion of osteoblasts associated with osseointegration, such as with BMSCs and the osteoblast-like cell line MC3T3 and HOB. , The surface morphology of Ti can be changed by preparing rough porous structures to create adhesion surfaces for BMSCs and MC3T3 cells, , and biologically active adhesion peptide sequences, such as RGD, , GFOGER, and FHRRIKA, can be loaded onto the Ti surface to improve the adhesion, proliferation, and viability of osteogenic-associated cells, and ultimately, promote the osseointegration of peri-implant osteoblasts.…”
Section: Static Modification Strategymentioning
confidence: 99%
“…Cell adhesion also plays a crucial role in the process of osseointegration. The main purpose is promoting the adhesion of osteoblasts associated with osseointegration, such as with BMSCs and the osteoblast-like cell line MC3T3 and HOB. , The surface morphology of Ti can be changed by preparing rough porous structures to create adhesion surfaces for BMSCs and MC3T3 cells, , and biologically active adhesion peptide sequences, such as RGD, , GFOGER, and FHRRIKA, can be loaded onto the Ti surface to improve the adhesion, proliferation, and viability of osteogenic-associated cells, and ultimately, promote the osseointegration of peri-implant osteoblasts.…”
Section: Static Modification Strategymentioning
confidence: 99%
“…Another research was carried out using strontium surface functionalization of specially designed titanium-niobium (Ti- 40 Nb) implant to accelerate bone growth by stimulating the osteoblasts and, at the same time, to inhibit the osteoclasts, which are responsible for bone resorption [ 68 ]. This remodeling process accelerated by the biomaterial may provide an advanced implant system that is mechanically adapted to the altered bone with the ability to stimulate bone formation.…”
Section: Mass Spectrometry Imaging Of Bone Implant Biomaterialsmentioning
confidence: 99%
“…It is an important aim to develop advanced metallic implants that are mechanically adapted to the weakened bone structure and ensure fast bone integration by modified surface characteristics. ToF-SIMS analysis of the Ti- 40 Nb surface after the release experiment revealed traces of residual strontium [68].…”
Section: Mass Spectrometry Imaging Of Bone Implant Biomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal ions, such as copper, silver, magnesium, strontium, etc., can promote osteogenesis and avoid certain toxicities by being carried with a slow-released coating film (76)(77)(78)(79). Van Hengel et al (80) indicated that the synergistic antibacterial effect could prevent infections by antibioticresistant bacteria.…”
Section: Coating Technologymentioning
confidence: 99%